Turkish Validity and Reliability of Readiness for Hospital Discharge Scale- Adult- Nurse Assesment Short Form - Manar Aslan (Association of Nurse Managers, 2020)
INTRODUCTION: This methodological study was carried out to determine whether the readiness for hospital discharge scale for adult patients- nurse assessment short form developed by Weiss and colleagues' in 2014 is a valid tool in Turkish. METHODS: The data of the study were collected from 160 patients and 160 nurses working in a public hospital between May and September 2019. RESULTS: Language validity, content validity (.98) and construct validity (≥.40) of the scale were performed. In reliability analysis, Pearson correlation, Cronbach alpha, parallel form reliability were performed. The goodness of fit of the model to the results was found to be acceptable. DISCUSSION AND CONCLUSION: Results of the study show tthat Turkish version of the scale can be used by the nurses as a scale that will provide an assessment of the readiness of the patients to discharge.